1989
DOI: 10.1002/1097-0142(19890701)64:1<178::aid-cncr2820640130>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Bladder carcinoma in patients age 40 years or younger

Abstract: The records of 26 men and nine women aged 40 years or younger, with transitional cell carcinoma of the bladder, were reviewed. Twenty-eight of the patients presented with gross painless hematuria, and 30 were regular smokers. Twenty-two patients presented with noninvasive disease, five with superficial invasion and eight with deep invasion. The risk of the disease progressing to invasion increased with the grade of the tumor, rising from 24% with Grade 1 to 75% with Grade 3. The patients younger than 30 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 12 publications
3
42
2
6
Order By: Relevance
“…In addition, other studies reported decreased recurrence and progression rates in younger patients as well (28,29,30,31,32). As opposed to this, there are also other studies that showed no significant difference between age (33,34,35). In our study, percentage of stage T2 patients were found to be significantly higher in age group 65-80 and over 80.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, other studies reported decreased recurrence and progression rates in younger patients as well (28,29,30,31,32). As opposed to this, there are also other studies that showed no significant difference between age (33,34,35). In our study, percentage of stage T2 patients were found to be significantly higher in age group 65-80 and over 80.…”
Section: Discussioncontrasting
confidence: 81%
“…Younger patients frequently present with lower grade and lower stage tumors than their elder counter parts (Wan, 1989). This is in contrast to the common belief that behaviour of cancer is more aggressive in younger age groups.…”
Section: Discussionmentioning
confidence: 67%
“…Transitional cancer of the bladder is a very rare malignancy in patients under 40 years (1-2.4% of all cancers) and among patients under 20 years it is extremely rare (0.1-0.4% of all bladder cancers) (ref. [3][4][5][6][7] ). According to a recent meta-analysis, only 103 bladder cancer patients under 20 years have been described.…”
Section: Discussionmentioning
confidence: 99%